Ancient genomes reveal the origin and evolutionary history of Chinese populations - Gao, Shizhu; Cui, Yinqiu (Frontiers in Earth Science, 2023)
Mitochondrial DNA was first successfully extracted from ancient remains approximately four decades ago. Research into ancient DNA has been revolutionized due to improvements in next-generation sequencing (NGS) technology in the early 21st century, as well as advances in the field of ancient DNA extraction and enhancement. In recent years, a large number of paleogenomic data has shed light on the origin and evolution of humans, and provided new insights into the migration and admixture events of populations, as well as the spread of languages and technologies. As China is located in the eastern part of Eurasia, it plays an integral role in exploration of the genetic history of Eurasians throughout the history of modern human habitation. Here we review recent progress deriving from paleogenomic analysis, which helps to reconstruct the prehistory of China.